Macroeconomic Determinants of Demand for Air Cargo Transport among Selected Airlines - Kiboi, Jane W; Katuse, Paul; Mosoti, Zachary (European Journal of Business and Strategic Management, 2017)
Purpose: The study sought to determine the effect of macroeconomic variables on the demand for air cargo for selected airlines. Methodology: The study target population was airlines across the World. The study used a sample of 10 airlines across the World as follows; Kenya airways, British airline, Ethiopian airlines, Emirate airlines, Qatar airways, Turkish airlines, South Africa Airlines, China Southern Airlines, Egypt airlines and Air France. For the purpose of this study, the GDP, interest rate (global) and the GDP, interest rate (domestic) for the home countries of each of the selected airlines were obtained from World Bank data. The countries included; Kenya, United Kingdom, Ethiopia, United Emirates, Qatar, Turkey, South Africa, China, Egypt and France. Secondary data of the selected airlines was collected from the International Air Transport Association (IATA) for the period from 2005 to 2014. The data collected was analyzed using STATA software to generate descriptive, trends and inferential statistics which were used to derive conclusions and generalizations regarding the population. The regression model was used to determine the impact of macroeconomic variables on demand for air cargo transport. Results: The findings revealed that Interest Rate (Domestic), Interest Rates (Global), GDP Growth Rate (Domestic) and GDP per capita (domestic) had a statistically significant relationship air cargo demand (ATK). The relationship between GDP Growth Rate (Domestic) and air cargo demand (ATK) was found to be positive and significant. Based on the findings the study concluded that macroeconomic variables both for origin countries and global economy have significant impacts on the air cargo demand. Unique contribution to practice and policy: The study recommends that airlines in air cargo business should carefully assess the macroeconomic performance of countries along their routes. Countries that have vibrant economic growth and low interest are ideal for cargo business. The study further recommended airlines in cargo business should only expand their routes and their freight capacity when their origin countries and global economy is performing excellently since economic growth impacts positively the demand for air cargo.